سياسة قطاع التكوين في الدمج المهني لبعض الفئات الخاصة من المجتمع الجزائري - جرو, حميدة (دفـاتر المـــــــــــخبـر; No 19 (2018): مجلة دفاتر, 2018)
يعتبر التكوين المهني من بين القطاعات المهمة في الدمج السوسيو-مهني لكل فئات المجتمع، لهذا تبرز أهمية الموضوع في الخدمات التكوينية التي يقدمها قطاع التكوين المهني بولاية بسكرة لفئات هشة، فكان هدف الورقة البحثية التعرف على دور التكوين المهني اتجاه هذه الفئات، ومن أهم النتائج التي تم توصل إليها أن التكوين المهني بولاية بسكرة عرف تطورات ملحوظ من 2004 إلى 2011 خاصة بالنسبة لفئات الثلاثة فئة المرأة الماكثة بالبيت وفئة السجناء، وفئة المعاقين وهذا بفضل الجهود المبذولة من طرف القطاع التكوين المهني بالولاية.  الكلمات المفتاحية: تكوين الفئات الخاصة، التكوين عن طريق جهاز المرأة الماكثة بالبيت، التكوين في الوسط السجني، دمج سوسيومهني، الفئات الهشة. The vocational training is one of the important sectors in the integration of Socio-professional all segments of society. This is why the importance of this subject stands in the training services which is provided by the vocational training sector in the state of Biskra to the fragile categories. Therefore, the aim of this paper was to identify the role of vocational training towards these categories. It was concluded that the vocational training in the state of Biskra was marked by remarkable developments from 2004 to 2011, especially for the three categories of housewives and prisoners and disabled thanks to the efforts exerted by the vocational training sector in the state. key words : The composition of the special categories, the composition by means of the woman's machinative apparatus in the house, the composition in the middle of the prison, the integration of sociogny, the fragile categories.